Gas diffusion layer made of water-jet entangled nonwoven fabric

The method of entangling carbon fiber webs with water of specific pH and conductivity levels in the gas diffusion layer manufacturing process addresses the issue of ion contamination in fuel cells, resulting in improved performance and longer service life.

JP2025511552AActive Publication Date: 2025-04-16CARL FREUDENBERG KG
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024555378
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-13
Filing Date
2023-05-09
Publication Date
2025-04-16
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

Existing gas diffusion layers (GDLs) for fuel cells often contain high concentrations of ions, particularly metal cations, which can contaminate the fuel cell membrane and affect its performance.

Method used

A method for manufacturing a gas diffusion layer using a carbon fiber or carbon fiber precursor web that is entangled with a water-containing fluid jet, where the water has a pH value between 5.5 and 8.0 and a conductivity of up to 250 microsiemens/cm, to produce a GDL with very low ion concentrations.

Benefits of technology

The resulting gas diffusion layer has a very low ion concentration, retains additives effectively, and maintains good mechanical properties, leading to improved fuel cell performance and extended service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511552000002
    Figure 2025511552000002
  • Figure 2025511552000003
    Figure 2025511552000003
  • Figure 2025511552000004
    Figure 2025511552000004
Patent Text Reader

Abstract

The present invention relates to a method for producing a gas diffusion layer, in which a web made of carbon fibers or a carbon fiber precursor is entangled with a water-containing fluid jet of a specific water quality, a gas diffusion layer obtainable by said method, and a fuel cell equipped with said gas diffusion layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a gas diffusion layer, in which a web made of carbon fibers or a carbon fiber precursor is entangled with a water-containing fluid jet of a specific water quality, a gas diffusion layer obtainable by said method, and a fuel cell equipped with said gas diffusion layer.

[0002] Background technology Fuel cells generate electrical energy by chemically reacting a fuel, particularly hydrogen, with oxygen to produce water. In a hydrogen-oxygen fuel cell, hydrogen or a hydrogen-containing gas mixture is fed to a positive electrode, where electrochemical oxidation occurs, releasing electrons (H2 → 2H + +2e - ). The protons are transported from the positive electrode chamber to the negative electrode chamber through a membrane that separates the reaction chambers airtight and electrically insulates them. The electrons supplied to the positive electrode are supplied to the negative electrode through an external conductor circuit. Oxygen or an oxygen-containing mixed gas is supplied to the negative electrode, and oxygen is reduced by the acceptance of electrons. The oxygen anions produced during this process react with the protons transported through the membrane to produce water (1 / 2O2 + 2H + +2e - →H2O).

[0003] Many applications, especially in automotive powertrains, use low-temperature proton exchange membrane fuel cells (PEMFCs), the core of which is a polymer electrolyte membrane (PEM), which converts protons (or oxonium ions, HO) +) and water, spatially separating the oxidant, usually atmospheric oxygen, from the reductant. A gas-tight, electrically insulating and proton-conducting membrane is provided with a catalyst layer on the positive and negative sides, which forms the electrodes and usually contains platinum as the catalytically active metal. The actual redox reactions and charge separation take place in this catalyst layer. The membrane and the catalyst layer form a unit, also called a catalyst coated membrane (CCM). On both sides of the CCM there are gas diffusion layers (GDLs), which stabilize the cell structure and are responsible for the transport and distribution of reactant gases, water, heat and electricity. The membrane, electrodes and gas diffusion layers form a membrane electrode assembly (MEA). Between these membrane electrode assemblies, flow divider plates (so-called bipolar plates) are arranged, which contain channels for the supply of process gas to the adjacent anode and cathode and usually also internal cooling channels.

[0004] The gas diffusion layer, located between the flow field plate and the catalyst layer, is crucial for the function and performance of the fuel cell. The process components consumed and produced in the electrode reactions must be transported through the gas diffusion layer and distributed homogeneously from the macrostructure of the flow field plate / bipolar plate to the microstructure of the catalyst layer. The electrons produced and consumed in the half-cell reactions must be conducted to the flow field plate with as little voltage loss as possible. The heat generated during the reactions must also be released to the coolant by the flow field plate, so the material of the GDL must also have a sufficient thermal conductivity. Furthermore, the GDL must also act as a mechanical compensator between the macrostructured flow field plate and the catalyst layer.

[0005] Gas diffusion layers for fuel cells typically consist of a carbon fiber substrate that is given a hydrophobic finish, usually with a fluoropolymer (e.g., PTFE), and then coated with a microporous layer (MPL). The MPL usually consists of a fluorine-containing polymer (e.g., PTFE) as a binder and a porous, electrically conductive carbon material (e.g., carbon black or graphite powder). Currently, three materials are used as carbon fiber substrates for GDLs: - Carbon fiber paper (a wet-laid, chemically bonded non-woven carbon fiber fabric containing a chemical binder and carbonized); - Woven carbon fibre fabrics (e.g. made from oxidized but not yet carbonised polyacrylonitrile fibre yarns which are then woven and subsequently carbonised or graphitised); - Carbon fiber nonwovens (for example, nonwovens made of oxidized polyacrylonitrile, drylaid, carded, water jet entangled, then sized and carbonized).

[0006] It is known that fuel cells can be contaminated by the introduction of foreign ions that are not involved in the electrode process. For example, the impact of bipolar plate materials and the cations and anions introduced from them into the fuel cell MEA on cell performance has been investigated. Other sources of metal cations in particular include emissions from other materials in the cell, system components such as tanks, heat exchangers, and piping, the air feed stream to the cathode, and hydrogen contamination from production and transportation. One potential problem with introduced metal ions is that they can be easily absorbed into the electrolyte membrane. This is because the affinity of metal cations for the sulfonic acid groups of the perfluorinated cation exchange membrane is strong, generally greater than the affinity of protons for the sulfonic acid groups.

[0007] It has now been found that the GDL can also contribute to the loading of foreign ions into the MEA. Thus, there is a need for a gas diffusion layer that contains very low concentrations of ions, particularly metal cations, and a method for making the same. In particular, it is desirable for the GDL to have very low concentrations of cations such as calcium, magnesium, sodium, and potassium ions that are typically found in industrial waters. It is desirable for other mechanical properties of the GDL to not be adversely altered.

[0008] For the production of carbon fiber nonwoven fabrics, webs made of carbon fibers or carbon fiber precursors can be entangled by the action of water-containing fluid jets. Such spunlacing methods for entanglement of webs by fluid jets or fluid streams (including spunlacing by superheated steam jets) are known to the person skilled in the art. One particular method for mechanical entanglement of nonwoven fabrics is water jet entanglement, in which high pressure water of about 20-400 bar or more is directed through a number of nozzles onto the web to be entangled. The impact force of the water jets then mechanically fixes the fibers to the product. So-called nozzle strips, which can be arranged in one or several rows, serve as tools for this method. Each row then has a number of nozzles. The maximum number of nozzles can be up to 20,000 nozzles per strip, with typical nozzle diameters of 0.05-0.3 mm.

[0009] WO 2021 / 170608 describes a method for producing a spunbond nonwoven fabric, in which the spunbond nonwoven fabric is subjected to water jet entanglement and, in a further sequence, to washing, in which fresh water can be supplied to the water jet entanglement and waste water from the water jet entanglement can be supplied to the washing. In general, fully demineralized water can be used as fresh water.

[0010] US 2003 / 182730 describes a nonwoven fabric with a low content of ionic impurities, which is achieved by washing with water with a low ionic concentration. The nonwoven fabric is used, among other things, for cleaning cloths and cleanroom protective clothing. The production of gas diffusion layers for fuel cells is not described.

[0011] WO 0231841 describes an electrically conductive nonwoven fabric obtained from fiber fluff of pre-oxidized carbon fibers by entangling the fiber fluff with a high-pressure fluid jet at a pressure of 100-300 bar, compressing the entangled fiber web and then carbonizing and / or graphitizing in a protective gas atmosphere at temperatures between 800°C and 2500°C.

[0012] DE 102006060932 A1 describes a temperature-stable structure comprising fibers and a coating, which is covalently bonded to the fiber surface. In particular, this is a conductive nonwoven fabric that is plasma-coated with a fluorinated hydrocarbon and is suitable as a gas diffusion layer for fuel cells. To produce the conductive nonwoven fabric, carbon fibers or carbon fiber precursors are layered to form a fiber fluff that is entangled by the action of a high-pressure fluid jet and then pre-dried, calendered and carbonized.

[0013] US Patent Application Publication No. 2019 / 0165379 describes a material for a gas diffusion layer based on a carbon fiber nonwoven fabric, which has areas of high and low basis weight in a plane, and at least one surface of the nonwoven fabric has a concave-convex pattern with concaves and convexities that are independent of the fiber weight distribution. The manufacture of the nonwoven fabric includes a water jet process.

[0014] None of the last four references mentions the quality of the water used in the waterjet process.

[0015] Unpublished international application PCT / EP2021 / 085452 (WO 2022 / 128895) describes a high purity gas diffusion layer and a method for its manufacture, in which a web of carbon fibers or carbon fiber precursors is entangled with a water-containing fluid jet, the water having a conductivity of up to 250 microsiemens / cm at 25° C. There is no mention of the pH value of the water used in the water jet treatment.

[0016] It has now been found that entanglement of dry-laid webs of carbon fibers or carbon fiber precursors by the action of a water-containing fluid jet allows the production of high quality and in particular high purity carbon fiber nonwoven fabrics. The quality of the water used for entanglement is extremely important.

[0017] Here, one of the important parameters for removing unwanted web-accompanying substances during wet entanglement, for example without the use of detergents, is the pH value of the water. At the same time, additives already added before this treatment step should be substantially retained. Optimization of the pH value can also reduce or prevent damage to the nonwoven fabric due to water treatment.

[0018] Another important parameter is the ion concentration, i.e. the proportion of dissociated substances dissolved in a certain amount of water. Surprisingly, by means of the water jet entanglement process it is possible to produce high purity nonwovens with a very low ion concentration, which can be further processed into GDLs, which also have a very low ion concentration. Advantageously, the resulting nonwovens are characterized by a very low number of so-called nozzle strip defects. Such defects can occur if individual nozzles of the nozzle strip are blocked.

[0019] Summary of the Invention A first subject of the invention is a method for producing a gas diffusion layer for a fuel cell, comprising the steps of: a) providing a fiber composition comprising carbon fibers and / or carbon fiber precursors, b) subjecting the fiber composition provided in step a) to a fiber fluff production process; c) entangling the fiber fluff by the action of a water-containing fluid jet to form a nonwoven fabric, the water used having a pH value in the range of 5.5 to 8.0; d) optionally subjecting the nonwoven fabric obtained in step c) to a thermal and / or mechanical treatment for drying and / or further entanglement, e) if the fiber composition used in step a) comprises a carbon fiber precursor, subjecting the nonwoven fabric to pyrolysis at a temperature of at least 1000°C.

[0020] In certain embodiments, the water used in step c) has a conductivity of up to 250 microSiemens / cm at 25°C.

[0021] In a further particular embodiment, the nonwoven fabric obtained in step c), d) or e) is (i.e. following the end of these steps, depending on which of these steps is carried out) subjected to a finishing treatment with a hydrophobizing agent (=step f)).

[0022] In a further particular embodiment, the nonwoven fabric obtained in step c), d), e) or f) is coated with a microporous layer (=step g)) (i.e. following the end of these steps, depending on which of these steps is carried out).

[0023] The present invention further relates to a fiber fluff (water-jet entangled nonwoven fabric) having a very low ion concentration, entangled by the action of a water-containing fluid jet. The subject of the present invention is therefore also the following: a) providing a fiber composition comprising carbon fibers and / or carbon fiber precursors, b) subjecting the fiber composition provided in step a) to a fiber fluff production process; c) The fiber fluff is entangled by the action of a water-containing fluid jet to form a nonwoven fabric, the water used having a pH value in the range of 5.5 to 8.0. The nonwoven fabric can be obtained by the method described above.

[0024] With regard to steps a), b) and c), reference is made in full to the following explanations regarding these steps.

[0025] A further subject of the invention is a gas diffusion layer as defined above and below or obtainable by the process as defined above and below.

[0026] A further subject of the invention is a fuel cell comprising at least one gas diffusion layer as defined above and below or obtainable by the method as defined above and below.

[0027] Detailed Description of the Invention Unless specified below, the pH values ​​given relate to a temperature of 25°C.

[0028] The determination of the pH value can be carried out by conventional methods known to those skilled in the art. Preferably, this determination is carried out by an electrical measurement method based on the measurement of the voltage of a unit of an electrochemical cell, one of the two half-cells being a measuring electrode and the other being a reference electrode. The potential of the measuring electrode depends on the pH value of the measuring solution. For the determination of the pH value, commercially available pH value measuring units based on a pH electrode and a reference electrode can be used, for example in the form of a combined measuring unit. A suitable method for determining the pH value is described in DIN EN ISO 10523-C5:2012-04 (Water quality - Measurement of pH value).

[0029] Measuring devices for measuring pH values ​​by proton activity, particularly those using electrical measurement methods such as commercially available pH value measuring units, generally have an automatic or manual temperature compensation section to compensate for the temperature dependence of the ionic products of water.

[0030] The gas diffusion layer obtained by the method according to the invention has the following advantages: - Optimizing the pH value of the water used for water jet entangling allows the removal of unwanted web entrainment materials during wet entangling without the use of cleaning agents, while at the same time substantially retaining additives already added before this treatment step, such as hard finishes, softeners, antistatic agents, hydrophobizing agents, antibacterial, antifungal or fungicidal finishes, flame retardants and other additives. - Optimizing the pH value can also reduce or prevent damage to the nonwoven fabric due to water treatment. - Carbon fiber nonwoven fabrics obtained by water jet entanglement from dry-laid carbon fibers and GDLs based on them are characterized by a very low ion concentration. - Nonwoven fabrics obtained from dry-laid carbon fiber precursors by water jet entanglement and subsequent carbonization or graphitization and GDLs based thereon are also characterized by a very low ionic concentration. The nonwoven fabrics obtained by water jet entangling according to the method of the invention have a very low number of so-called nozzle strip defects. Compared to the GDLs conventionally used in the prior art, the GDLs according to the invention have comparable and better mechanical properties. Fuel cells based on the GDL according to the invention have a longer service life than fuel cells based on conventional GDL.

[0031] The gas diffusion layer according to the present invention and obtainable by the method according to the present invention comprises a carbon fiber nonwoven fabric as a planar conductive material. The carbon fiber nonwoven fabric and the gas diffusion layer are planar structures having a substantially two-dimensional, planar extent, but a relatively small thickness. The gas diffusion layer has a base surface, which generally substantially corresponds to the base surface of the adjacent membrane with the catalyst layer and the base surface of the adjacent flow field plate of the fuel cell. The shape of the base surface of the gas diffusion layer may be, for example, polygonal (n-gonal with n≧3, such as triangle, square, pentagon, hexagon, etc.), circular, circular segment-shaped (for example, semicircular), elliptical, or elliptical segment-shaped. Preferably, the base surface is rectangular or circular.

[0032] Gas diffusion layer manufacturing Process a) In step a) of the method according to the invention a fibre composition is provided which comprises carbon fibres and / or carbon fibre precursors.

[0033] Preferred carbon fibers are composed of at least 90% by weight, preferably at least 92% by weight, of carbon based on their total weight. In a particular embodiment, graphitized carbon fibers can be used. These carbon fibers have a higher carbon content, in particular at least 95% by weight, of carbon.

[0034] Suitable precursors of carbon fibres are fibres of synthetic or natural origin that can be converted into carbon fibres by one or more process steps (carbonisation). These include, for example, fibres made of polyacrylonitrile homo- and copolymers (PAN fibres), phenolic resins, polyesters, polyolefins, cellulose, aramids, polyetherketones, polyetheresterketones, polyethersulfones, polyvinyl alcohols, lignin, pitch and mixtures thereof. Preferably, the fibre composition provided in step a) comprises PAN fibres as precursor fibres or consists of PAN fibres as precursor fibres. In a first preferred embodiment, the fibre composition provided in step a) comprises PAN fibres and other fibres, which are advantageously selected from fibres made of phenolic resins, polyesters, polyolefins, cellulose, aramids, polyetherketones, polyetheresterketones, polyethersulfones, polyvinyl alcohols, lignin, pitch and mixtures thereof. Such additional polymers are advantageously contained in the carbon fibre precursor in an amount of up to 50% by weight, particularly preferably up to 25% by weight, relative to the carbon fibre precursor. In a second preferred embodiment, the fiber composition provided in step a) consists exclusively of PAN fibers.

[0035] Suitable PAN fibers are selected from PAN homopolymers, PAN copolymers and mixtures thereof. The PAN copolymers contain at least one comonomer introduced by polymerization, which is advantageously selected from (meth)acrylamides, alkyl acrylates, hydroxyalkyl acrylates, alkyl ether acrylates, polyether acrylates, alkyl vinyl ethers, vinyl halides, vinyl aromatics, vinyl esters, ethylenically unsaturated dicarboxylic acids, their mono- and diesters, and mixtures thereof. For example, the comonomer is selected from acrylamide, methyl acrylate, methyl methacrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-octyl acrylate, lauryl acrylate, stearyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2-methoxyethyl acrylate, 4-methoxybutyl acrylate, diethylene glycol ethyl ether acrylate, 2-butoxyethyl acrylate, ethyl vinyl ether, acrylic acid, methacrylic acid, itaconic acid, itaconic acid monomethyl ester, itaconic acid monolauryl ester, fumaric acid dimethyl ester, styrene, vinyl acetate, vinyl bromide, vinyl chloride, etc. When polyacrylonitrile copolymer fibers are used as carbon fiber precursors in step a), the proportion of the comonomer is up to 20% by weight, preferably up to 10% by weight, based on the total weight of the monomers used in the polymerization. Preferably, polyacrylonitrile homopolymer fibers are used as carbon fiber precursors in step a).

[0036] PAN polymers can be spun, for example, from a solution by wet spinning and coagulation into filaments, which can then be bundled together into strands (fiber bundles). PAN copolymers often have a lower melting point than PAN homopolymers, making them suitable for use in melt spinning as well as wet spinning processes. The PAN fibers thus obtained are usually subjected to oxidative cyclization (also called oxidation or stabilization for short) in an oxygen-containing atmosphere at elevated temperatures of about 180-300°C. The resulting chemical crosslinks improve the dimensional stability of the fibers.

[0037] The fibers obtained during oxidative cyclization can be used as carbon fiber precursors in step a) without further workup. The fibers obtained during oxidative cyclization can also be advantageously subjected to at least one workup step selected from cleaning, coating with at least one sizing agent, drying and a combination of at least two of these treatment steps. To clean the fibers after electrochemical oxidation, they can be subjected to a washing process. This washing is carried out in particular to remove fiber fragments. The washing is usually followed by a drying step. To modify the surface properties, the fibers can be at least partially coated with at least one sizing agent. The sizing agent can be used, for example, in the form of a solution in a suitable solvent or in the form of a dispersion. The fibers can be passed, for example, through a sizing bath to apply the coating. The sizing agent can be at least partially peeled off from the fibers during the water jet entanglement in step c). If the water used for entanglement of the fiber fluff in step c) is at least partially recycled, it can be advantageous to subject the wastewater resulting from the water jet entanglement to a workup for partial or complete removal of the sizing agent contained in the wastewater.

[0038] After the fibers have been coated with at least one size, they are usually subjected to (further) drying, which can be carried out for example using hot air, a hot plate, heated rollers or radiant heaters, respectively.

[0039] The carbon fiber precursors thus obtained can be used as fiber compositions in step a) of the method according to the invention and further processed. Also, the fiber compositions comprising or consisting of PAN fibers can be subjected to pyrolysis at a temperature of at least 1000° C., whereby the PAN precursors are converted into carbon fibers. With regard to the pyrolysis conditions, reference is made to the following explanation for step e). The carbon fibers thus obtained can likewise be used as fiber compositions in step a) of the method according to the invention and further processed.

[0040] Step b) In step b) of the method according to the invention, the fiber composition provided in step a) is subjected to a fiber fluff (carbon fiber web or carbon fiber precursor web) production process. Suitable methods for producing nonwoven fabrics are known to the person skilled in the art and are described, for example, in H. Fuchs, W. Albrecht, Vliesstoffe, 2. Aufl. 2012, S. 121 ff., Wiley-VCH. These include, for example, dry-laid, wet-laid, extrusion and solvent processes. In a preferred embodiment, the fiber fluff is produced by subjecting the fiber composition provided in step a) to a dry-laid process in step b). The production of dry-laid nonwoven fabrics can in principle be carried out using a carding process or an aerodynamic process. In the carding process, the formation of the fiber fluff is carried out by a card or carding machine, whereas in the aerodynamic process, the formation of the web is carried out with air from the fibers. If desired, the fiber fluff can be stacked in several layers to form a web. The drylaid process of step b) may involve modifying the properties, for example by stretching the web, which may allow, for example, thickness calibration of the web and / or pre-entanglement of the fiber fuzz.

[0041] Process c) In step c) of the method according to the invention, the fiber fluff obtained in step b) is entangled to form a nonwoven fabric by the action of a water-containing fluid jet, which also includes a fluid stream and a steam jet.

[0042] In principle, the mechanical entanglement methods known for this purpose, also called spunlace methods, are suitable for water jet entanglement. In principle, the so-called steam jet technique, which uses superheated steam jets for web entanglement, is also suitable. Such methods are known to the person skilled in the art. In a particular mechanical entanglement method for nonwovens, water at high pressure of about 20-500 bar is directed through a number of nozzles to the web to be entangled. The nozzles are then arranged in one or more rows in so-called nozzle strips. These nozzle strips have a number of nozzles in each row. The maximum number of nozzles can be up to 20000 nozzles per strip, typical nozzle diameters being 0.05-0.5 mm. The nozzle hole diameters usually have only very small tolerances, for example less than 2 mm. In order to obtain a defect-free nonwoven, it is necessary that the nozzle hole diameter does not change during operation, and in particular that the nozzles do not become blocked.

[0043] It has been found that the pH value of the water used for entangling the fiber fluff (web) is important for the quality of the gas diffusion layer for fuel cell applications produced therefrom. It is therefore an important feature of the method according to the invention that the water used for entangling the nonwoven fabric in step c) has a pH value (at 25° C.) in the range of 5.5 to 8.0, preferably in the range of 5.5 to 7.0, particularly preferably in the range of 6.0 to 6.9.

[0044] Furthermore, it has been found that the electrical conductivity of the water used for entangling the fiber fluff (web) is also important for the quality of the gas diffusion layer for fuel cell applications produced therefrom.Thus, advantageously, the water used for entangling the nonwoven fabric in step c) has an electrical conductivity of at most 250 microsiemens / cm (μS / cm) at 25°C.Particularly preferably, the water used in step c) has an electrical conductivity of at most 200 microsiemens / cm at 25°C, particularly at most 150 microsiemens / cm at 25°C, and especially at most 100 microsiemens / cm at 25°C.

[0045] Electrical conductivity is an index of the ion concentration, i.e. the proportion of dissociated substances dissolved in a certain amount of water. Here, the electrical conductivity depends, among other things, on the concentration of the dissolved substances, their degree of dissociation, the valence and mobility of the cations and anions formed, as well as on the temperature. The measurement of electrical conductivity is based on the ohmic resistance of the water sample to be analyzed, or on the reciprocal of the resistance, the electrical conductivity (unit: Siemens S = Ω). -1 Conductivity is based on the determination of the conductivity (S / cm). Commercially available conductometers can be used to measure conductivity. Measurements are usually given in S / cm (Siemens per centimeter) or, for water samples with low ionic load, in microsiemens per centimeter.

[0046] Process water or process water for industrial processes is usually supplied from public drinking water networks or pumped from wells, rivers and lakes. Drinking water and process water used in processes where water quality is important are usually controlled for their composition and, if necessary, subjected to a water treatment process. Here, the requirements for water purity are extremely diverse depending on the respective field of application. For example, drinking water is supplied as a colorless, transparent liquid, free of odors and harmful microorganisms and substances, but rich in essential minerals and salts. This water has food quality, but is not necessarily suitable for many industrial applications. According to the German Drinking Water Ordinance (TrinkwV 2001, revised version of 10 March 2016), drinking water in Germany must have a pH value in the range of 6.5 to 9.0, usually 7.0 to 8.5. According to the German Drinking Water Ordinance, the limit value for conductivity is 2790 microsiemens / cm at 25 °C. The electrical conductivity of tap water supplied by German water supplies is between 250 and 1000 microsiemens / cm at 25 °C, depending on the hardness level. The main inorganic cations are Na + , K + , Ca 2+ and Mg 2+ It is.

[0047] Preferably, the water used in step c) contains up to 200 ppm by weight, particularly preferably up to 25 ppm by weight of Na. + It has an ion content.

[0048] Preferably, the water used in step c) contains up to 200 ppm by weight, particularly preferably up to 10 ppm by weight of K. + It has an ion content.

[0049] Preferably, the water used in step c) contains up to 10 ppm by weight of Mg 2+ It has an ion content.

[0050] Preferably, the water used in step c) contains up to 200 ppm by weight, particularly preferably up to 40 ppm by weight of Ca. 2+ It has an ion content.

[0051] To provide the water used in step c) according to the invention, available drinking water or process water can be subjected to a work-up to adjust the pH value and / or reduce the ion concentration, including membrane processes such as ion exchange, electrodeionization, nanofiltration, reverse osmosis, electrodialysis, distillation, thermal treatments such as flash evaporation.

[0052] In a first preferred embodiment, nanofiltration, reverse osmosis or a combination of these processes are used to reduce the ion concentration. Both nanofiltration and reverse osmosis are based on the fact that the water to be treated passes through a semipermeable membrane under a pressure higher than the osmotic pressure, resulting in a permeate with a reduced ion concentration. Here, nanofiltration is carried out at a lower pressure than reverse osmosis, so the purification capacity is lower than that of reverse osmosis membranes, but is sufficient in many cases. It is also possible to carry out a pre-purification by nanofiltration and then further reduce the ion concentration by reverse osmosis.

[0053] In a second preferred embodiment, an ion exchange process is used to reduce the ion concentration. For this purpose, available drinking or process water (raw water) is typically contacted with at least one cation exchange resin and at least one anion exchange resin. In a suitable embodiment, the raw water is first treated with at least one strongly acidic cation exchanger to convert the cations present in the water into hydrogen ions (H+ The water thus obtained is then treated with at least one strongly basic anion exchanger to exchange the negatively charged ions for hydroxide ions (OH - ) is exchanged. If necessary, the water obtained after contact with the cation exchanger can be further contacted with at least one weakly basic anion exchanger before the strongly basic exchanger. If necessary, after the cation exchanger or between the weakly basic anion exchanger and the strongly basic anion exchanger, if present, the water can be subjected to a carbon dioxide degassing treatment.

[0054] To adjust the properties of the water used in step c), it is also possible to mix two or more starting waters with different compositions, which differ in at least one property, such as the pH value or the content of certain ions. In a particular embodiment, to adjust the pH value of the water used in step c), a mixture of at least one water with a pH value lower than the target value and at least one water with a higher pH value is used. In a very particular embodiment, to adjust the pH value of the water used in step c), a mixture of at least one water with a low pH value obtained by nanofiltration or reverse osmosis and at least one water with a high pH value obtained by ion exchange is used.

[0055] What is important with regard to the pH value of the water used in step c) is the content of CO2 and the dissociation of carbonic acid produced therefrom. Here, the hydrogen carbonate anion (HCO2) is produced by the first dissociation step from CO2 and water, which occurs in the pH range of 4.3 to 8.2. 3- ) and oxonium ion (HO +The formation of ) is of particular importance for the method according to the invention. In drinking or process water, the concentration of dissolved carbon dioxide ranges from a few milligrams per liter to more than 20 mg / l, depending on the source. The concentration of bicarbonate anion in drinking or process water can be several hundred g / l, depending on the source. Pure water is mostly slightly acidic in pH value due to the absorption of carbon dioxide from the surrounding air, while distilled water can reach an acidic pH value of about 5.8. Freshly produced distilled water only has a pH value of about 7, but after contact with carbon dioxide it reaches a slightly acidic pH value within a few hours.

[0056] The effect of dissolved carbon dioxide on the pH value depends on the method selected for the work-up of the raw water. The bicarbonate anions can be effectively separated from the raw water, for example, by processes such as ion exchange, nanofiltration, reverse osmosis, etc. This is not the case with dissolved CO2, which is not substantially retained by the membranes used, for example, for nanofiltration or reverse osmosis. As a result, the permeate of the nanofiltration or reverse osmosis membrane generally has an acidic pH value due to the dissociation of dissolved carbon dioxide, which can be completely below pH 6. Furthermore, the conductivity increases accordingly, due to the subsequent generation of bicarbonate in this case from the dissolved CO2. Thus, in certain embodiments, the raw water can be subjected to a carbon dioxide degassing treatment before being treated with a nanofiltration or reverse osmosis membrane.

[0057] For example, a CO2 degasser can be used for the degassing of carbon dioxide, where water is passed through a column and strip air is fed in countercurrent, thereby removing CO2 from the water. Alternatively or additionally, a membrane degassing process can be used for the degassing of carbon dioxide.

[0058] In a particular embodiment of the method according to the invention, the water used for entangling the fiber fluff in step c) is partially or completely recycled.The method according to the invention thus allows a reduction in the amount of fresh water required for water jet entangling and the amount of waste water to be disposed of.In this case, it is ensured that the water used for treating the fiber fluff always has a conductivity within the range of the invention and that contamination of the fiber fluff with components contained in the waste water of the water jet entangling is otherwise avoided.For this purpose, the waste water of the water jet entangling can be partially or completely subjected to work-up and / or exchanged.

[0059] Work-up and / or replacement of the wastewater from the water jet entanglement can be carried out continuously or at intervals.

[0060] Preferred is a method in which the fiber fluff is entangled by the action of a water-containing fluid jet to form a nonwoven fabric, a wastewater stream is discharged from the fiber fluff treatment, a target value for the conductivity of the wastewater stream is defined, an actual value for the conductivity of the wastewater stream is examined, and after a limit value for the deviation of the actual value from the target value is reached, the wastewater stream is at least partially subjected to work-up and / or exchange with water having a low ion concentration and the wastewater stream is at least partially returned to the fiber fluff treatment.

[0061] For work-up, the wastewater stream can be subjected to ion concentration reduction as described above. Additionally, the wastewater stream can be subjected to further purification, for example to remove fibers and fiber debris.

[0062] Step d) If necessary, the nonwoven fabric obtained in step c) can be subjected to a thermal and / or mechanical treatment for drying and / or further entanglement. Suitable drying methods are convection drying, contact drying, radiant drying and combinations thereof.

[0063] Preferably, the nonwoven fabric obtained in step c) is subjected to a treatment by calendering. Calendering allows further thermal entanglement of the nonwoven fabric and at the same time allows its thickness calibration. Here, several web layers can also be bonded together. In a particular embodiment, the nonwoven fabric obtained in step c) comprises thermoplastic fibers, which act as bonding fibers and are generally carbonizable. In this case, the nonwoven fabric obtained by calendering can be thermally bonded in step d) to form bonding sites, where the fibers are plasticized and fused (thermal bonding).

[0064] Process e) If the fiber composition used in step a) contains carbon fiber precursors, the nonwoven fabric is subjected to pyrolysis at a temperature of at least 1000°C in step e). Depending on the temperature during pyrolysis, a distinction is made between carbonization and graphitization. Carbonization is a treatment at about 1000-1500°C under an inert gas atmosphere, in which the volatile products are decomposed. Graphitization, i.e. heating to about 2000-3000°C under inert gas, results in so-called highly elastic or graphite fibers. The proportion of carbon increases during pyrolysis, for example from about 67% by weight when treated at temperatures below 1000°C to about 99% by weight when treated at temperatures above 2000°C. In particular, the fibers obtained by graphitization are highly pure, lightweight, strong and have very good electrical and thermal conductivity.

[0065] Process f) Optionally, following steps c), d) or e), the nonwoven fabric can be finished with at least one additive, advantageously selected from hydrophobizing agents f1), conductivity-enhancing additives f2), further additives f3) different from f1) and f2), and mixtures thereof.

[0066] Preferably, the nonwoven fabric is coated and / or impregnated (finished) with a hydrophobizing agent f1) comprising at least one fluorine-containing polymer. Preferably, the fluorine-containing polymer is selected from polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), perfluoroalkoxy polymer (PFA) and mixtures thereof. Perfluoroalkoxy polymer is, for example, a copolymer of tetrafluoroethylene (TFE) and perfluoroalkoxy vinyl ether, such as perfluorovinylpropyl ether. Preferably, polytetrafluoroethylene is used as the fluorine-containing polymer.

[0067] Preferably, the mass proportion of the fluorine-containing polymer f1) is 0.5 to 40%, particularly preferably 1 to 20%, in particular 1 to 10%, relative to the mass of the nonwoven fabric. In a specific embodiment, the fluorine-containing polymer is PTFE and the mass proportion is 0.5 to 40%, preferably 1 to 20%, in particular 1 to 10%, relative to the mass of the nonwoven fabric.

[0068] In many cases, the nonwoven fabric already has good electrical and thermal conductivity due to the carbon fibers used, even without the conductivity-improving additive. However, in order to improve the electrical and thermal conductivity, the nonwoven fabric can be further finished with at least one conductivity-improving additive f2). Preferably, the nonwoven fabric is finished with a conductivity-improving additive f2) selected from metal particles, carbon black, graphite, graphene, carbon nanotubes (CNTs), carbon nanofibers and mixtures thereof. Preferably, the conductivity-improving additive f2) comprises or consists of carbon black. The finishing of the nonwoven fabric with at least one conductivity-improving additive f2) can be carried out, for example, together with polymers f1) and / or further additives f3). Preferably, an aqueous dispersion is used for the finishing of the nonwoven fabric.

[0069] Preferably, the weight proportion of the conductivity improving additive f2) is 0.5-45%, preferably 1-25%, based on the weight of the nonwoven fabric. In a particular embodiment, the conductivity improving additive f2) comprises or consists of carbon black and has a weight proportion of 0.5-45%, preferably 1-25%, based on the weight of the nonwoven fabric.

[0070] The nonwoven fabric may further be finished with at least one further additive f3). These include, for example, polymer binders, surface-active substances, etc., different from components f1) and f2). Suitable binders f3) are, for example, furan resins, etc. In particular, the nonwoven fabric may further be finished with at least one polymer different from f1), preferably using high-performance polymers. The further polymer f3) is preferably selected from polyaryletherketones, polyphenylene sulfides, polysulfones, polyethersulfones, semi-aromatic (co)polyamides, polyimides, polyamideimides, polyetherimides and mixtures thereof. The finishing of the nonwoven fabric with at least one additive f3) may be carried out, for example, together with polymer f1) and / or conductivity-improving additive f2). The binder f3) may be subsequently cured, if necessary. This may be carried out, for example, together with drying and / or sintering after the finishing with polymer f1) or separately from this.

[0071] Preferably, the total mass proportion of the further additives f3) is 0-80%, preferably 0-50%, relative to the mass of the nonwoven fabric. If the nonwoven fabric further comprises at least one further additive f3), the total mass proportion of the further additives f3) is 0.1-80%, preferably 0.5-50%, relative to the mass of the nonwoven fabric.

[0072] The nonwoven fabric advantageously has a thickness in the range of 50 to 500 μm, particularly preferably 100 to 400 μm, said thickness relating to the nonwoven fabric in its unfinished, uncompressed state, i.e. before the GDL is incorporated into the fuel cell.

[0073] The finishing of the nonwoven fabric with components f1), f2) and / or f3) can be carried out using application methods known to the person skilled in the art, in particular coating and / or impregnation. Advantageously, for coating and / or impregnation of the nonwoven fabric, a method selected from padding, doctor blade processing, spraying, slope padding and combinations thereof is used.

[0074] In the padding process, the nonwoven fabric is passed through a padder (dipping tank) with a solution or dispersion containing the additive, and then squeezed by a pair of rollers whose pressure and, if necessary, gap can be adjusted to achieve the desired dosage of the additive.

[0075] In the doctor blade process, a distinction is made between gravure printing and screen printing. In gravure printing, the doctor blade is, for example, a sharpened steel blade with or without a backup blade. It is used to scrape off the excess additive-containing solution or dispersion that adheres to the web of the impression cylinder (doctor blade removal). In screen printing, on the other hand, the doctor blade is usually made of rubber or plastic and has sharp or rounded edges.

[0076] In spray application, the additive-containing solution or dispersion is applied to the nonwoven fabric to be finished by means of at least one nozzle, in particular at least one slot nozzle.

[0077] The slope padding process (kiss roll) is preferably used to coat the underside of a horizontally extending web of material. The coating medium can be applied in the opposite direction or in the same direction to the web. By means of a transfer roller, indirect coating can be achieved with small application amounts.

[0078] In a particular embodiment, the nonwoven fabrics which have been finished with components f1), f2) and / or f3) in step f) of the process according to the invention are subjected to drying and / or heat treatment. Suitable processes for drying and / or heat treatment of nonwoven fabrics coated and / or impregnated with additive-containing solutions or dispersions are known in principle. Preferably, the drying and / or heat treatment is carried out at temperatures in the range from 20 to 250° C., particularly preferably from 40 to 200° C. Furthermore, drying can be carried out under reduced pressure.

[0079] Process g) In a preferred embodiment, the gas diffusion layer according to the invention consists of a two-layer composite based on a nonwoven fabric and a microporous layer (MPL) applied on one side of the nonwoven fabric. Accordingly, in the production of the gas diffusion layer, the nonwoven fabric obtained in steps c), d), e) or f) can be coated with a microporous layer.

[0080] In contrast to macroporous nonwovens, MPLs are microporous, with pore sizes usually significantly below 1 micrometer, preferably at most 900 nm, particularly preferably at most 500 nm, in particular at most 300 nm. The average pore size of MPLs is advantageously in the range of 5 to 200 nm, particularly preferably 10 to 100 nm. The measurement of the average pore size can be carried out by mercury porosimetry. MPLs contain conductive carbon particles, advantageously carbon black or graphite, in a matrix of a polymer binder. Preferred binders are the fluorine-containing polymers mentioned above, in particular polytetrafluoroethylene (PTFE).

[0081] The microporous layer advantageously has a thickness in the range of 10 to 100 μm (micrometers), particularly preferably 20 to 50 μm. This thickness relates to the uncompressed state of the microporous layer B), i.e. before the GDL is integrated into the fuel cell.

[0082] The gas diffusion layer according to the invention advantageously has a thickness (total thickness of nonwoven fabric and MPL) in the range of 80 to 1000 μm, particularly preferably 100 to 500 μm, said thickness relating to the uncompressed state of the GDL, i.e. before the GDL is integrated into the fuel cell.

[0083] A further subject of the invention is a fuel cell comprising at least one gas diffusion layer as defined above or obtainable by the method as defined above. In principle, the gas diffusion layer according to the invention is suitable for all types of conventional fuel cells, in particular for low-temperature proton exchange membrane fuel cells (PEMFC). Full reference is made to the above-mentioned embodiments for the structure of the fuel cell. [Brief description of the drawings]

[0084] [Figure 1] FIG. 1 shows the metal contents (Ca2+, Na+, Mg2+ and K+) of untreated nonwoven fabrics and nonwoven fabrics entangled with water of different conductivity. [Diagram 2] FIG. 1 shows the Ca2+ ion and Na+ ion contents of a base nonwoven fabric entangled with water of various electrical conductivities, a carbon fiber nonwoven fabric obtained by carbonizing the base nonwoven fabric, and a gas diffusion layer obtained by applying MPL. [Diagram 3] FIG. 3 is a graph showing the total content of Ca2+ ions and Na+ ions, similar to FIG. 2.

[0085] The invention will now be illustrated by the following examples which should not be construed as limiting.

[0086] Working Example The metal content (Ca) of the base nonwoven fabric made of oxidized polyacrylonitrile fibers, the carbonized nonwoven fabric obtained from it, and the GDL 2+ , Na + , Mg 2+ and K. +The measurements of ) were carried out using the ICP-AES method (Inductively Coupled Argon Plasma - Atomic Emission Spectrometry). Sample preparation (for digestion) can be carried out according to EPA Method 3050A for Acid Digestion of Sediments, Sludges and Soils. The process includes the following steps: 1.) Nitric acid digestion at 95°C for 15 minutes 2.) Add more nitric acid and continue decomposition for another hour. 3.) Remove from hot plate and add deionized water and 20% hydrogen peroxide solution. 4.) Heat again on the hot plate for about 15 minutes, and once the bubbles have completely stopped forming, remove from the hot plate again. 5.) Add concentrated hydrochloric acid and decompose again for 1 hour.

[0087] For water jet entanglement, water with a conductivity according to Table 1 below was used. Comparative water 1 corresponds to the process water customarily used in conventional water jet web entanglement processes. In water batches 2 and 3, the ion concentration was reduced by nanofiltration.

[0088] [Table 1]

[0089] Manufacturing Example To produce the base nonwoven, drylaid fiber fluff made of 100% oxidized polyacrylonitrile fibers was carded. The fiber fluff was fed to an entanglement unit where the fibers were spunlaced from both sides and entangled with each other using high energy water jets at a pressure of about 100 bar in the first stage and about 200 bar in the second stage. The water quality shown in Table 1 was used. The nonwoven was dried and wound up, with a basis weight of 150 g / m after water jet entanglement and drying. 2The thickness of the water-jet entangled nonwoven fabric was then reduced to 0.25 mm by subjecting the nonwoven fabric to thickness calibration. The nonwoven fabric was then fed to a carbonization unit, where it was carbonized at approximately 1000-1400°C under a nitrogen atmosphere.

[0090] To apply the finish to the nonwoven fabric, an impregnation composition was used that contained 70% carbon black and 30% PTFE on a solids basis. The finish was applied at a concentration of 15% (15 g / m) relative to the mass of the GDL substrate. 2 The nonwoven fabric was then dried at 160°C and sintered at 400°C. The resulting MPL loading was 24 g / m2. 2 It was.

Claims

1. A method for manufacturing a gas diffusion layer for a fuel cell, comprising the steps of: a) providing a fiber composition comprising carbon fibers and / or carbon fiber precursors; b) subjecting the fiber composition provided in step a) to a fiber fluff production process; c) entangling said fiber fluff by the action of a water-containing fluid jet to form a nonwoven fabric, the water used having a pH value in the range of 5.5 to 8.0; d) optionally subjecting the nonwoven fabric obtained in step c) to a thermal and / or mechanical treatment for drying and / or further entanglement, e) if the fiber composition used in step a) comprises a carbon fiber precursor, subjecting the nonwoven fabric to pyrolysis at a temperature of at least 1000° C.

2. 2. The process according to claim 1, wherein the water used for entangling the fiber fluff in step c) has a pH value in the range of 5.5 to 7.0, particularly preferably in the range of 6.0 to 6.

9.

3. 3. The method according to claim 1 or 2, wherein the water used for entangling the fiber fluff in step c) has a conductivity of at most 250 microSiemens / cm at 25°C, preferably at most 200 microSiemens / cm at 25°C, in particular at most 150 microSiemens / cm at 25°C.

4. 4. The process according to claim 1, wherein the nonwoven fabric obtained in step c), d) or e) is further finished (step f)) with at least one additive, preferably selected from hydrophobizing agents f1), conductivity enhancing additives f2), further additives f3) and mixtures thereof.

5. 5. The method according to claim 1, wherein the nonwoven fabric obtained in step c), d), e) or f) is further coated with a microporous layer (step g)).

6. 6. The method of claim 1, wherein the fiber composition provided in step a) comprises a carbon fiber precursor selected from non-oxidized polyacrylonitrile fibers, oxidized polyacrylonitrile fibers, and mixtures thereof.

7. 7. The method according to any one of claims 1 to 6, wherein the fibre composition provided in step a) further comprises further fibres selected from fibres made of phenolic, polyester, polyolefin, cellulose, aramid, polyetherketone, polyetheresterketone, polyethersulfone, polyvinyl alcohol, lignin, pitch and mixtures thereof.

8. 7. The process according to claim 1, wherein the fiber composition provided in step a) consists of polyacrylonitrile fibers, in particular polyacrylonitrile homopolymer fibers.

9. 9. The method according to any one of claims 1 to 8, wherein the fiber composition provided in step a) is subjected to a drylaid process in step b) to produce fiber fluff.

10. 10. The method according to claim 1, wherein the water used for entangling the fiber fluff in step c) is at least partially recycled.

11. 11. The method according to claim 10, further comprising the steps of: entangling fiber fluff by the action of a water-containing fluid jet to form a nonwoven fabric; discharging a wastewater stream from the treatment of the fiber fluff; defining a target value for the electrical conductivity of the wastewater stream; examining an actual value for the electrical conductivity of the wastewater stream; and, after reaching a limit value for the deviation of the actual value from the target value, at least partially subjecting the wastewater stream to work-up and / or exchange with water having a low ion concentration, and at least partially returning the wastewater stream to the treatment of the fiber fluff.

12. 12. The method according to any one of claims 1 to 11, wherein the nonwoven fabric obtained in step c) is subjected to further entanglement in step d) by calendering.

13. 13. The method according to claim 4, wherein the hydrophobizing agent f1) comprises at least one fluorine-containing polymer.

14. 14. The method of claim 4, wherein the conductivity enhancing additive f2) is selected from metal particles, carbon black, graphite, graphene, carbon nanotubes (CNTs), carbon nanofibers and mixtures thereof.

15. 15. The process according to claim 4, wherein the further additives f3) are selected from polymer binders different from components f1) and f2), surface-active substances and mixtures thereof.

16. 16. The method according to claim 4, wherein the nonwoven fabric is subjected to a heat treatment during or after the coating and / or impregnation with the hydrophobizing agent in step f1).

17. below: a) providing a fiber composition comprising carbon fibers and / or carbon fiber precursors; b) subjecting the fiber composition provided in step a) to a fiber fluff production process; c) The fiber fluff is entangled by the action of a water-containing fluid jet to form a nonwoven fabric, the water used having a pH value in the range of 5.5 to 8.0, preferably in the range of 5.5 to 7.0, particularly preferably in the range of 6.0 to 6.

9. A nonwoven fabric obtainable by the method of claim 1.

18. 18. The nonwoven fabric according to claim 17, wherein the water used in step c) has a conductivity of at most 250 microSiemens / cm at 25°C, preferably at most 200 microSiemens / cm at 25°C, in particular at most 150 microSiemens / cm at 25°C.

19. A gas diffusion layer obtainable by the method according to any one of claims 1 to 16.

20. A fuel cell comprising at least one gas diffusion layer obtainable by the method according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Pearl amino acid spunlace non-woven fabric and preparation method thereof

    CN114381861A

  • Water stream interlaced nonwoven fabric and its production

    JP1987223355A

  • Hydrophilic carbon fiber sheetlike material, carbon fiber electrode material and method for producing the same

    JP2003213563A

  • Catalyst and method for producing acrylic acid

    JP2004160342A

  • conductive nonwoven fabric

    JP2004511672A